All That Glitters Is Not Grit: Three Studies of Grit in University Students - Kannangara, Chathurika S.; Allen, Rosie E.; Waugh, Gill; Nahar, Nurun; Khan, Samia Zahraa Noor; Rogerson, Suzanne; Carson, Jerome (Frontiers in Psychology, 2018)
The present research looked at the importance of the concept of grit in University students based on a mixed-method approach. Study 1 comprised 440 University students. All were given the Grit Scale, the Perceived Stress Scale, the short Warwick Edinburgh Mental Well-being Scale, the Office of National Statistics Well-being items and the Self-Control Scale. Levels of grit were significantly higher in female students, older students and postgraduates. Grit correlated highest with self-control. Study 2 looked at 340 University students. In addition to measuring self-control, mental wellbeing and grit, measures of resilience and mindsets were also added. A construct validity test of the grit scale showed that high grit scorers had significantly higher levels of self-control and mental well-being, were more resilient and were more likely to have a more growth oriented mindset. Grit varies with age and is most closely associated with the concept of self-control. The third study was a qualitative investigation with ten successful graduates. Semi-structured interviews were coded using thematic analysis. Three broad themes emerged. The first, Passion and Perseverance, included themes of having short and long terms goals, resilience, dedication and endurance. The second, Self-Control, included time management, self-awareness, prioritising tasks and knowing strengths and weaknesses. The third theme identified was Positive Mindsets. This included having a positive attitude towards learning, the importance of feedback and constructive criticism and that success is not materialistic. The qualitative research has helped “unpack” concepts from the grit research and may enable University tutors to guide students better. Though these studies were only conducted in one English University, they have been stepping stones in our quest to discover what are the most important factors in determining student academic success? The development and piloting of our new Uni-stride Scale, is the next step in this process.